Combustion Chemistry Diagnostics for Cleaner Processes. Issue 38 (21st July 2016) - Kohse‐Höinghaus, Katharina
Abstract: Climate change, environmental problems, urban pollution, and the dependence on fossil fuels demand cleaner, renewable energy strategies. However, they also ask for urgent advances in combustion science to reduce emissions. For alternative fuels and new combustion regimes, crucial information about the chemical reactions from fuel to exhaust remains lacking. Understanding such relations between combustion process, fuel, and emissions needs reliable experimental data from a wide range of conditions to provide a firm basis for predictive modeling of practical combustion processes. Abstract : Emission control : In‐situ molecular‐beam mass spectrometry (see above) is instrumental for the detection of numerous reactive intermediates in reactors and flames to understand the combustion process.